2014
DOI: 10.1016/j.jbiomech.2013.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Antigen removal for the production of biomechanically functional, xenogeneic tissue grafts

Abstract: Xenogeneic tissues are derived from other animal species and provide a source of material for engineering mechanically functional tissue grafts, such as heart valves, tendons, ligaments, and cartilage. Xenogeneic tissues, however, contain molecules, known as antigens, which invoke an immune reaction following implantation into a patient. Therefore, it is necessary to remove the antigens from a xenogeneic tissue to prevent immune rejection of the graft. Antigen removal can be accomplished by treating a tissue w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 81 publications
0
28
0
Order By: Relevance
“…The primary outcome measure for success of decellularization procedures has been evaluation of tissue acellularity on microscopy and more recently DNA quantification. 3,21,29 However, previous studies by our group and others have demonstrated both the existence of non-cellular antigenic components and that cellular antigens may persist in apparently acellular scaffolds. 3,12,26,29 Consequently, the goals in production of a potentially ideal xenogeneic cECM scaffold are to remove cellular elements and reduce antigenicity of the biomaterial, while maintaining structure, composition and functional properties of the cECM niche.…”
Section: Discussionmentioning
confidence: 88%
“…The primary outcome measure for success of decellularization procedures has been evaluation of tissue acellularity on microscopy and more recently DNA quantification. 3,21,29 However, previous studies by our group and others have demonstrated both the existence of non-cellular antigenic components and that cellular antigens may persist in apparently acellular scaffolds. 3,12,26,29 Consequently, the goals in production of a potentially ideal xenogeneic cECM scaffold are to remove cellular elements and reduce antigenicity of the biomaterial, while maintaining structure, composition and functional properties of the cECM niche.…”
Section: Discussionmentioning
confidence: 88%
“…After isolation from the donor, these grafts are gamma-irradiated to kill the resident cells in an effort to eliminate the graft's potential to stimulate an immune response in the recipient. However, it has been suggested that decellularization of tissues, including cartilage, does not remove all antigenic materials [74,75]. While the use of IHRGs is considered safe, the incidence of IHRG resorption (31%) has been reported to be significantly greater than that of autologous costal cartilage (3%) [73,76].…”
Section: 3: Allogeneic Graftsmentioning
confidence: 99%
“…The purpose of irradiating allogeneic rib cartilage is to kill the resident chondrocytes in an effort to reduce the immune potential of the grafts. However, there is evidence that, despite cell death, antigen-containing cell remnants remain and are difficult to remove due to the density of the cartilaginous ECM [74,75]. While chondrocytes express major histocompatibility antigens (MHCs) types I and II which have the potential to trigger an immune response, chondrocytes reside in lacunae where they do not easily encounter immune cells.…”
Section: : Perspectives and Future Directionsmentioning
confidence: 99%
“…Further, harsh processing techniques that break down larger macromolecules present naturally in the extracellular matrix can result in unwanted tissue reactions. Similarly, residues of detergents or other processing agents used can stimulate degradative inflammation and aberrant healing processes, leading to overt rejection of the implant, prolonged inflammation and foreign body reaction that can result in chronic pain or inappropriate tissue integration that can lead to eventual mechanical instability (Cissell et al, 2014).…”
Section: Structurally Correct and Functional Repairmentioning
confidence: 99%